Hot-spring inputs and climate drive dynamic shifts in archaeal communities in Lake Magadi, Kenya Rift Valley - E. R. Collins; T. M. Ferland; I. S. Castañeda; R. B. Owen; T. K. Lowenstein; A. S. Cohen; R. W. Renaut; M. D. O'Beirne; J. P. Werne (Biogeosciences)
The methane index (MI) is an organic geochemical index that uses isoprenoid glycerol dialkyl glycerol tetraethers (GDGTs) as a proxy for methane cycling. Here, we report results from sediments in core MAG14-2A that span almost 500 ka in Lake Magadi, Kenya. The deposits show abrupt shifts between high and low MI values through calcareous, tuffaceous and zeolitic silts. The MI switches “off” (MI < 0.2) and “on” (MI > 0.5) through the core with bulk organic matter enriched in 13C during “MI-off” periods (∼ −18 ‰) in the upper part of the core, whereas 13C is lower (−22 ‰ to −25 ‰) in lower parts of the sedimentary sequence. Sediments deposited when the MI switches “on” showed δ13COM values as low as −89.4 ‰, but most values were within the range of −28 ‰ to −30 ‰, which is consistent with contributions from methanogens rather than methanotrophs. Thus, the likely source of these high MI values in Lake Magadi is methanogenic archaea. Our results show that hydrothermal inputs of bicarbonate-rich waters into Lake Magadi combined with further evaporative concentration cause a shift in the dominant archaeal communities, alternating between two stable states.